VD_FINDINFO Jug / 2016 / 168 vom 9. November 2015 - VD Tribunal cantonal (2015)
DÉLIT DE CHAUFFARD, RADAR, EXCÈS DE VITESSE, FIXATION DE LA PEINE | 47 al. 1 CP, 90 al. 4 LCR, 8 al. 1 let. a OOCCR-OFROU